Correction to: Patient and Surgeon Expectations Prior to Anterior Cruciate Ligament Reconstruction. Issue 1 (February 2019) - Khair, Mahmoud Michael; Ghomrawi, Hassan; Wilson, Sean; Marx, Robert G.
The degree of author Hassan Ghomrawi was listed incorrectly in the original article. It is correct here.